Urinary tract infection in febrile children without any obvious focus of infection and the methods of diagnosis - E. T. Kavin Kardhikh; N. Aishwarya Lakshmi; V. SriSanthanaKrishnan; G. Manigandan (Global Journal of Medicine and Public Health, 2024)
Background The purpose of this study was to assess the prevalence of urinary tract infection (UTI) and the validity of routine microscopic urine analysis, enhanced urine analysis, urine dipstick and urine culture in the diagnosis of UTI among febrile children aged 1 month to 5 years who presented without any focus of infection.